Analisis Manajemen Kearsipan dan Kualitas Sumber Daya Manusia terhadap Mutu Pelayanan Administrasi di Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung - Libra Hayatin; Sriwahyuni Mega Hastuti (Otonomi, 2023)
In carrying out operational activities, the administration section needs to be supported by good archival management, because it can assist employees in managing data, maintenance activities, and others, to improve the quality of administrative services. The purpose of this study was to analyze the effect of archives management and the quality of human resources on the quality of administrative services. This research used quantitative method. This research was conducted at UIN Sayyid Ali Rahmatullah Tulungagung. The sampling technique used Non-Probability Sampling. The number of samples used 62 education staff/respondents. Data comes from questionnaires. Data analysis using SPSS software. The results of the study show that there is an effect of archival management and the quality of human resources on the quality of administrative services at UIN Sayyid Ali Rahmatullah Tulungagung. The magnitude of the partial influence of archival management on (r) is indicated by a Beta of 0.315 (31.5%) with a t count of 2.890 and sig. of 0.005 (significance at the 1% level), the hypothesis which states that there is an influence of records management on the quality of administrative services is acceptable. Furthermore, the magnitude of the partial influence of the quality of human resources on (r) is indicated by a Beta of 0.434 (43.4%) with a t count of 3.978 and sig. of 0.000 (significance at the 1% level), the hypothesis stating that there is an effect of the quality of human resources on the quality of administrative services is acceptable.